Automatic Quantification of Extra-Medial Thickness in Carotid Ultrasound - Zahnd, Guillaume; Skilton, Michael; Navab, Nassir (IEEE International Ultrasonics Symposium, IUS, 2018)
Ultrasound imaging of the carotid artery is one of the most widely used technique to assess cardiovascular burden. Nevertheless, the established 'intima-media thickness' index fails to reflect some structural modifications that accompany atherosclerotic disease progression. For this reason, the 'extra-medial thickness' (EMT)index has been put forward, and was demonstrated to be associated with cardiovascular risk factors. The aim of this article is to present an automated framework based on contour segmentation to quantify the EMT. The method is based on a dual-step dynamic programming scheme to extract unambiguously the anatomical interfaces from different regions bearing a similar anatomical structure. Applied in vivo on 35 participants, the average accuracy was 115 ± 196 μm. Accordingly, the proposed method shows promising performance to perform automatic quantified measurements toward cardiovascular risk evaluation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiovascular risk; Carotid artery; Contour segmentation; Dynamic programming; Ultrasound